EVALUACIÓN DE LAS CARACTERÍSTICAS FÍSICAS-QUÍMICAS DE UNA BEBIDA PROTEICA A BASE DE SOYA (Glycine max) Y GUANÁBANA (Annona muricata) - TRIANA RIVAS, ARON VICENTE (2025)
This research focuses on the development of a protein-rich beverage based on soy (Glycine max) and soursop (Annona muricata) as a nutritious and accessible alternative in Ecuador, where sustainability challenges and access to protein sources are significant